Symbolic Poetry, Inspired Myths and Salvific Function of Allegoresis in Proclus’ Commentary on the Republic - Domaradzki, Mikołaj (Peitho. Examina Antiqua, 2014)
The present article is concerned with Proclus’ highly original and profoundly influential account of the symbolic function of poetry, the pedagogic as well as the hieratic value of myths and the soteriological power of allegorical interpretation. Thus, the paper begins with a brief discussion of Plato’s dismissal of poetry as μέγιστον ψεῦδος. Subsequently, Proclus’ theory of three kinds of poetry is examined, upon which attention is paid to his revolutionary idea that σύμβολα rather than μιμήματα are the tools of the highest kind of poetry. Then, Proclus’ views on the difference between Plato’s and Homer’s μυθοποιΐα are considered. While the article concludes with an analysis of Proclus’ conviction about the functional similarity of symbols in myths and those in magic rites, allegoresis is shown to have the same salvational role that Proclus ascribes to theurgy.